A 3D‐Bioprinted Vascularized Glioblastoma‐on‐a‐Chip for Studying the Impact of Simulated Microgravity as a Novel Pre‐Clinical Approach in Brain Tumor Therapy. Issue 11 (2nd August 2021) - Silvani, Giulia; Basirun, Carin; Wu, Hanjie; Mehner, Christine; Poole, Kate; Bradbury, Peta; Chou, Joshua
Abstract: Glioblastoma multiforme (GBM) is one of the most aggressive malignant brain tumors and urgently requires the development of new therapeutic strategies. In this study, an innovative hybrid in vitro vascularized GBM‐on‐a‐chip model is presented as a strategic integration of microfluidics and 3D bioprinting technologies. The system can recreate the compartmentalized brain tumor microenvironment, comprising the functional blood brain barrier (BBB) and the adjacent 3D perivascular tumor niche, by selectively mimicking physiological shear stress and cell–cell, cell–matrix mechanical interaction. The GBM‐on‐a‐chip model was evaluated under simulated microgravity (µG) condition as a form of mechanical unloading showing a significant cell morphological and mechanotransduction response thereby indicating that gravitational forces play an important role in glioblastoma mechanical regulation. The proposed GBM‐on‐a‐chip represents a meaningful biological tool for further research in cancer mechanobiology and pre‐clinical approach in brain tumor therapy. Abstract : A hybrid vascularized glioblastoma (GBM)‐on‐a‐chip comprising functional blood brain barrier together with 3D bioprinted tumor was established to recreate the compartmentalized brain tumor micro‐environment. The GBM‐on‐chip was tested under simulated microgravity which elucidated the important role of mechanotransduction in tumor regulation and demonstrated the GBM chip to represent an impactful biological tool in brain cancer mechanobiology.